Referral Appropriateness for Transesophageal Echocardiography and its Diagnostic Impact in a Tertiary Care Hospital - Hoque, Mohammed Shahidul; Khaled, Md Fakhrul Islam; Osmany, Din E Mujahid Mohammad Faruque; Hasan, Md Nazmul; Salam, Abdus; Tuhin, Md Shahadat Hossain; Ahmed, Choudhury Meshkat (University Heart Journal, 2025)
Introduction: This study aimed to evaluate the suitability of referrals for transesophageal echocardiography test in a tertiary care hospital, based on the appropriate use criteria (AUC) established by the American College of Cardiology Foundation and the American Society of Echocardiography, which were released in 2011, and their diagnostic consequences. Method: A one-year cross-sectional observational study was carried out in a tertiary-level hospital. Adult TEE indications were independently evaluated by two cardiologists using the AUC. Based on the pertinent guidelines, each study was classified as appropriate, inappropriate, or uncertain, and their diagnostic implications for patient management were assessed. Diagnostic impact was defined by any change in diagnostic work-up or therapeutic decisions induced by TEE results. Result: Of the 120 patients, the mean age of the study patients was 39.6±14.75 years. The study showed a significant correlation between age group and the appropriateness of TEE referrals (p<0.001). The younger age group had the highest percentage of suitable referrals (34.6%). The study determined that 65% of the requested TEE were appropriate, 25% were inappropriate and 10% were deemed questionable. Conclusion: In an ideal scenario, a diagnostic cardiovascular imaging test like a TEE should impact clinical management, provided it is correctly ordered for the appropriate patient. Using AUC in TEE can directly influence diagnostic outcomes since appropriate studies are more likely to uncover significant new insights and lead to healthcare interventions. University Heart Journal 2025; 21(1): 42-49